Gravity-driven membrane (GDM) reactors with biocarriers for enhancement of Icelandic wastewater treatment - Ihtisham ul haq Shami 1993- (2021)
With low temperatures across the year in Iceland, secondary biological treatment of wastewater faces a challenge. Gravity-driven membrane (GDM) filtration of municipal wastewater presents an alternative solution for decentralized and centralized secondary treatment of wastewater in Iceland. This study aims to investigate the performances of three GDM reactors which were packed with different types of biocarriers (synthetic fibre, lava rocks and lava sand respectively). The GDM reactors were operated in parallel, and each reactor operation was divided into 4 different phases in terms of water head, cleaning protocol, and temperature. Phase IV, with 2-3 days cleaning protocol and lower reactor temperature, provided highest flux recovery for all the membranes as well as highest average normalized flux. Water quality analysis showed that GDM process could efficiently remove organic matter and nutrients from the wastewater, allowing the effluent of the process to meet the European Union (EU) discharge standards. Cake layer resistance was the dominant fouling resistance, with an average of 89.9% of overall fouling resistance, throughout the study. Finally, economic analysis of GDM reactors was performed based on the study’s results, focusing on the capital and operational cost of a treatment plant with a population range of 10-5000 people. The economic analysis revealed that proposed GDM with synthetic fibre biocarriers had the lowest total cost per person per year as well as the lowest energy consumption per year, and proposed GDM with lava sand biocarriers had highest total cost per person per year as well as highest energy consumption per year. Með lág hitastig allt árið í kring, annars stigs hreinsun skólps á við vand að stríða við íslenskar aðstæður. Þyngdaraflsdrifnar himnur (GDM) sem ætlaðar eru til að sía heimilisskólp er kynntar sem valkostur fyrir dreifða og miðlæga annar stigs hreinsun, fyrir skólphreinsun á Íslandi. Í þessari ritgerð var markmiðið að rannsaka afkastagetu þriggja mismunandi GDM líftanka ...